The accuracy (A) and reaction time RT (B) as a function of the search condition for control participants and patients with CI (different bars). - Mohammed M. Alnawmasi (11156577) (2025)
The accuracy (A) and reaction time RT (B) as a function of the search condition for control participants and patients with CI (different bars).